Zmiany w dochodach ludności wielozawodowej na wsi niemieckiej w latach 1980-1995 - Mossakowska, Ewa (Zeszyty Naukowe SGGW - Ekonomika i Organizacja Gospodarki Żywnościowej, 1997)
In 1980-1995 total income of multi-vocational population in Germany was higher, both in nominal and real terms, than of those receiving only agricultural income. The share of agricultural income in total income of multi-vocational households decreased, while the others (non-agricultural gainful activity, social payments) increased. Incomes of multi-vocational agricultural households were differentiated by type of production and location. The level of their disposable income was also relatively higher in the surveyed period.